2020
DOI: 10.5217/ir.2020.00002
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 gene variants and thiopurine-induced leukopenia in patients with inflammatory bowel disease

Abstract: Thiopurine has been used to maintain remission and to reduce antidrug antibody formation in monoclonal antibody therapy in patients with inflammatory bowel disease (IBD). The use of thiopurine is limited by side effects such as leukopenia. Thiopurine S-methyltransferase (<i>TPMT</i>) variants are associated with thiopurine-induced leukopenia in Westerners, but the frequency of the risk alleles is low in Asians. Recently, a variant in the nudix hydrolase 15 (<i>NUDT15</i>) gene (R139C, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…The frequency of NUDT15 polymorphism in this study was similar to that reported in previous studies in the East Asian population. 9,12,14 The development of AEs was more frequent in patients with C/T and T/T genotypes than in those with the C/C genotype. Patients with the T/T genotype should avoid thiopurine treatment because almost all of these patients experience severe AEs such as early severe leukopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of NUDT15 polymorphism in this study was similar to that reported in previous studies in the East Asian population. 9,12,14 The development of AEs was more frequent in patients with C/T and T/T genotypes than in those with the C/C genotype. Patients with the T/T genotype should avoid thiopurine treatment because almost all of these patients experience severe AEs such as early severe leukopenia.…”
Section: Discussionmentioning
confidence: 99%
“…12 Therefore, genotyping of NUDT15 R139C is considered the best way to predict thiopurine-induced AEs in Asian patients. 11,14 Thiopurines should be contraindicated in patients with the T/T genotype because several studies have reported that almost all of these patients treated with thiopurines develop severe leukocytopenia and alopecia. 10,15 Patients with the C/T genotype also have a higher risk of dose-dependent AEs than patients with the C/C genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to consider preventive strategies against adverse events while considering thiopurine therapy in elderly UC patients. NUDT15 gene variants should be routinely tested before initiating thiopurine therapy to avoid serious myelotoxicity from thiopurines 42 . Avoiding prolonged use of thiopurines and combination with anti‐tumor necrosis factor (TNF) agents may also reduce the risk of adverse events.…”
Section: Medical Therapy Of Elderly Ulcerative Colitismentioning
confidence: 99%
“…NUDT15 gene variants should be routinely tested before initiating thiopurine therapy to avoid serious myelotoxicity from thiopurines. 42 Avoiding prolonged use of thiopurines and combination with anti‐tumor necrosis factor (TNF) agents may also reduce the risk of adverse events.…”
Section: Medical Therapy Of Elderly Ulcerative Colitismentioning
confidence: 99%
“…Cytopenias, especially leucopenia, are recognized as a dose-dependent adverse effect of thiopurines. Cytopenias have been reported with a variable frequency in patients with thiopurine use and may result in significant treatment discontinuation and occasional morbidity [ 4 ]. Various enzymes like thiopurine S-methyltransferase (TPMT), xanthine oxidase and hypoxanthine phosphoribosyl transferase are enzymes involved in the metabolism of thiopurines [ 9 ].…”
Section: Introductionmentioning
confidence: 99%